Tourist preferences for whale watching and rule changes in the Salish Sea - Schamp, Abby; Morzaria-Luna, Hem Nalini; Knox, Melissa; Anderson, Christopher M. (Ocean & coastal management, 2025)
Wildlife tours are subject to many viewing restrictions, especially when viewing endangered species. Viewing regulations can impact demand for tours, local communities that depend upon tourism income, and the wildlife. We use a discrete choice experiment to estimate how changes in tour attributes affects Salish Sea tourist willingness to pay for whale watching tours. We find that tourists are willing to pay average ticket prices to view Southern Resident Killer Whales, transient killer whales, or humpback whales. Our results indicate that tourists are willing to pay the most to view orcas from a close viewing distance for at least 40 min with less boats in proximity. We estimate changes in ticket demand of up to 7% due to changes in tour whale viewing distance. [Display omitted]